Oral health status and treatment needs among school children in Sana’a City, Yemen - Al-Haddad, Khaled Abdulsalam; Al-Hebshi, Nezar Noor; Al-Ak’hali, Mohammed Sultan (Wiley, 2010)
This study assessed dental caries, treatment needs, and gingival health among 1,489 school children aged 6-14 years in Sana’a City, Yemen, using standard WHO oral survey methods. The findings indicated high prevalence of caries, gingivitis, and treatment needs.